2018
DOI: 10.3389/fpls.2018.01356
|View full text |Cite
|
Sign up to set email alerts
|

Does Late Maturity Alpha-Amylase Impact Wheat Baking Quality?

Abstract: Late maturity α-amylase (LMA) and pre-harvest sprouting (PHS) are both recognized as environmentally induced grain quality defects resulting from abnormally high levels of α-amylase. LMA is a more recently identified quality issue that is now receiving increasing attention worldwide and whose prevalence is now seen as impeding the development of superior quality wheat varieties. LMA is a genetic defect present in specific wheat genotypes and is characterized by elevated levels of the high pI TaAMY1 α-amylase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 44 publications
2
53
3
Order By: Relevance
“…The greater the amount of alphaamylase, the faster the stirrer will fall, determining low values of HFN. An additional cause for high alpha-amylase activity is late maturity alpha-amylase, which is a genetic defect existing in some genotypes related to rapid temperature change after flowering (Newberry et al, 2018).…”
Section: Control Of Milling Quality and Alpha-amylase Activity Of Wheatmentioning
confidence: 99%
“…The greater the amount of alphaamylase, the faster the stirrer will fall, determining low values of HFN. An additional cause for high alpha-amylase activity is late maturity alpha-amylase, which is a genetic defect existing in some genotypes related to rapid temperature change after flowering (Newberry et al, 2018).…”
Section: Control Of Milling Quality and Alpha-amylase Activity Of Wheatmentioning
confidence: 99%
“…Marti, Cardone, Nicolodi, Quaglia, and Pagani () also reported that adding a small amount of sprouting wheat (less than 2%), which provided α‐amylase, improved bread volume and softness because starch hydrolysates are beneficial to yeast fermentation, which leads to enhanced bread baking quality (Marti et al., ). LMA‐affected wheat, with an increase of two to three times the hydrolytic activity compared with unaffected wheat, did not have a significantly negative impact on bread quality; although that wheat has reduced FNs (for example, 210 to 240 seconds) (Newberry et al., ).…”
Section: Falling Numbermentioning
confidence: 99%
“…At this time, no study has reported on any detrimental effects of LMA on end-product quality. The first comprehensive evaluation of LMA on bread quality (Newberry et al, 2018) reported a lack of correlation between bread baking traits, FN and LMA affected grain. These authors demonstrated that an elevated level of α-amylase in grains reduced the FN values of flour; however, no significant correlation was found between low LMA-FN and poor end-product quality, in terms of oven spring, loaf weight, loaf volume or any other quality parameters of breads processed using low and high FN wheat flours (ranging from 157 to 234 s, and from 250 to 300 s respectively).…”
Section: Introductionmentioning
confidence: 99%